2000
DOI: 10.1038/sj.leu.2401634
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance factors in acute myeloid leukemia: a comparative analysis

Abstract: To compare the clinical relevance of drug resistance factors in de novo acute myeloid leukemia (AML), we determined their relationship to both response to induction chemotherapy and survival of the patients in univariate as well as multivariate analyses. The drug resistance factors immunocytochemically studied in 111 patients at the time of diagnosis included the lung resistance protein (LRP), P-glycoprotein (P-gp), multidrug resistance protein (MRP1) and bcl-2. In the univariate analyses, age (P = 0.005), kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…Clinical resistance to therapy is also associated with an increased expression of Mcl-1 in adult ALL 15 and Bcl-2 expression in acute myeloid leukemia. 16 In contrast, a recent report showed that increased expression of the proapoptotic Bax in childhood ALL at diagnosis is associated with an increased risk of relapse. 17 The mechanisms by which p53 promotes apoptosis are not fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…Clinical resistance to therapy is also associated with an increased expression of Mcl-1 in adult ALL 15 and Bcl-2 expression in acute myeloid leukemia. 16 In contrast, a recent report showed that increased expression of the proapoptotic Bax in childhood ALL at diagnosis is associated with an increased risk of relapse. 17 The mechanisms by which p53 promotes apoptosis are not fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…35 On the other hand, there is currently no information on specific cytogenetic abnormalities in PB/PC-F. 36 In anthracyclin-resistant disease, multidrug resistance genes might also play a role. 37 Of note, 'activated B-like' DLBCLs defined by microarray screening also have a poor prognosis. 10,11 Since PB/PC-F relapses early and seems to be refractory to PSCT, these patients might be candidates for alternative treatment strategies like allogeneic bone marrow transplantation or additional B-cell antibody therapy.…”
Section: Pb/pc-f Are Associated With Poor Clinical Outcome and Resistmentioning
confidence: 99%
“…4 High expression of Bcl-2, an anti-apoptotic protein, can be associated with drug resistance in hematological malignancies. 4,11,[36][37][38][39][40][41][42][43][44][45][46][47] Thus, even the lower expression of Bcl-2 in some samples could provide an optimal anti-apoptotic effect. The role of Bcl-2 as a prognostic indicator remains controversial and it has therefore been suggested that Bcl-2 should be evaluated in parallel with other apoptotic markers.…”
Section: Leukemiamentioning
confidence: 99%